Electrochemically Catalyzed Decarboxylative Borylation of (Hetero)Aryl Carboxylic Acids - Tian, Yan; Li, Yingchao; He, Yucan; Xu, Zu; Yuan, Yulu; Xu, Bo; Kong, Xianqiang (Synthesis)
A straightforward and efficient electrochemical method for the decarboxylative borylation of (hetero)aryl carboxylic acids has been outlined. This metal-/base-/oxidant-free strategy enables efficient access to arylboronate esters, demonstrating broad substrate scope (20 examples) with yields up to 62% while maintaining exceptional atom- and step-economy.